Regulating network-based industries: the case of telecommunications - Henning Klodt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
A mandatory open-network-provision (ONP) by dominant firms is the appropriate government regulation in the presence of network externalities. For basic telephone services and online services, a permanent ONP regulation seems indispensable, whereas telecommunication networks only require transitional ONP regulation as long as public or privatized PTTs dispose of a dominant market position. Regulatory institutions tend to prefer either cost-plus or price-cap contracts for defining appropriate price-ceilings for network-access under ONP regulation. In order to avoid the specific disadvantages of both, governments should better apply incentive contract schemes which allow a sharing of efficiency gains among producers and customers.
Keywords: D82; L51; L96; 330; Telekommunikationspolitik; Telekommunikationsinfrastruktur; Netzzugang; Markteintritt; Regulierung; Theorie